2010
DOI: 10.1128/jvi.02709-09
|View full text |Cite
|
Sign up to set email alerts
|

Residues Surrounding the Glycosylphosphatidylinositol Anchor Attachment Site of PrP Modulate Prion Infection: Insight from the Resistance of Rabbits to Prion Disease

Abstract: Prion diseases are a group of transmissible, invariably fatal neurodegenerative diseases that affect both humans and animals. According to the protein-only hypothesis, the infectious agent is a prion (proteinaceous infectious particle) that is composed primarily of PrP Sc , the disease-associated isoform of the cellular prion protein, PrP. PrP Sc arises from the conformational change of the normal, glycosylphosphatidylinositol (GPI)-anchored protein, PrP C . The mechanism by which this process occurs, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…Moreover, the expression of these proteins in a transgenic model animal allowed us to collect data on multiple, relevant in vivo assays, including locomotor activity, neuronal degeneration, subcellular distribution, and a battery of biochemical/structural tests. Notably, our studies generally agree with observations in purified in vitro systems describing the different conformational stability of hamster, mouse, and rabbit PrP (11,29,32,33). These experiments are typically performed with the globular domain of the prion protein, so providing in vivo context with the full-length protein is critical.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, the expression of these proteins in a transgenic model animal allowed us to collect data on multiple, relevant in vivo assays, including locomotor activity, neuronal degeneration, subcellular distribution, and a battery of biochemical/structural tests. Notably, our studies generally agree with observations in purified in vitro systems describing the different conformational stability of hamster, mouse, and rabbit PrP (11,29,32,33). These experiments are typically performed with the globular domain of the prion protein, so providing in vivo context with the full-length protein is critical.…”
Section: Discussionsupporting
confidence: 78%
“…First, there are many differences between hamster and rabbit PrP (9 in the globular domain and 22 in the mature protein), obscuring the contribution of each residue to the structure of the protein. Amino acid substitutions from the RaPrP sequence into the N-terminal unstructured domain, the globular domain and the C-terminal region containing the GPI anchor, prevent the conversion of MoPrP into PrP Sc (6,29). Second, it is unclear which interactions between amino acids may contribute to the overall stability of the protein, and therefore, single amino acid substitutions may not reveal fundamental insight about the three-dimensional structure of PrP.…”
Section: Discussionmentioning
confidence: 99%
“…Christen et al (15) have inferred that the interaction between these two conformational markers could act as regulators of the functional specificity of PrP C . The study reported by Hill and co-workers (68) suggests that the rabbitspecific residues surrounding the C-terminal glycosylphosphatidylinositol anchor may interfere with a PrP Sc interaction site.…”
Section: Discussionmentioning
confidence: 99%
“…Nisbet et al showed that by exchanging amino acids at the C-terminal moiety within the SS-GPI of murine PrP C (MoPrP) by the ones of rabbit PrP C (RbPrP, rabbits are naturally relatively resistant to prion infection 59 ), the resulting MoPrP-RbGPI becomes resistant to PrP Sc conversion. 60 Interestingly, studies coming from the group of Bate and Williams showed that modifications in the lipid part of the GPIanchor or of the sialic acid residue lead to alterations in cholesterol at the plasma membrane and to reduced PrP Sc loads and infectivity (these experiments are discussed below in the section "Signaling Through PrP C "). In vivo, the scenario becomes more complex.…”
mentioning
confidence: 99%